2014
DOI: 10.1165/rcmb.2013-0338rc
|View full text |Cite
|
Sign up to set email alerts
|

2-O, 3-O-Desulfated Heparin Inhibits Neutrophil Elastase–Induced HMGB-1 Secretion and Airway Inflammation

Abstract: Neutrophil elastase (NE) is a major inflammatory mediator in cystic fibrosis (CF) that is a robust predictor of lung disease progression. NE directly causes airway injury via protease activity, and propagates persistent neutrophilic inflammation by upregulation of neutrophil chemokine expression. Despite its key role in the pathogenesis of CF lung disease, there are currently no effective antiprotease therapies available to patients with CF. Although heparin is an effective antiprotease and anti-inflammatory a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 41 publications
0
53
0
Order By: Relevance
“…secretion into cell culture media. Importantly, we demonstrated that ODSH blocks NE release of HMGB1, at least in part, by inhibiting NE activity (17). In this report, we tested whether ODSH inhibited HMGB1 release from RAW264.7 cells when triggered by NE or by LPS, an inflammatory mediator.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…secretion into cell culture media. Importantly, we demonstrated that ODSH blocks NE release of HMGB1, at least in part, by inhibiting NE activity (17). In this report, we tested whether ODSH inhibited HMGB1 release from RAW264.7 cells when triggered by NE or by LPS, an inflammatory mediator.…”
Section: Discussionmentioning
confidence: 89%
“…Classically, HMGB1 is either secreted by macrophages and other airway cells after infection (11), inflammation (17), and oxidative stress (33,34), or released from necrotic cells, attracting neutrophils to necrotic tissues (35). Neither of the inflammatory stimuli used to activate HMGB1 release from RAW264.7 cells caused macrophage cell death, so HMGB1 was released by signaling mechanisms, resulting in secretion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, strategies disrupting TGF-b1/Smad signaling undoubtedly have therapeutic potential in the clinical treatment of PF. High-mobility group box 1 (HMGB1) is a transcription factor-like protein that acts as a danger signal in inflammatory diseases, tissue injury, as well as fibrotic diseases (Rowe et al, 2008;Ebina et al, 2011;Ogiku et al, 2011;Lee et al, 2013;Griffin et al, 2014;Li et al, 2014a). In lung tissues from patients with PF, HMGB1 is predominantly expressed in alveolar macrophages, infiltrating inflammatory cells, and epithelial cells (Hamada et al, 2008).…”
Section: Introductionmentioning
confidence: 99%